The Effect of Puzzle Therapy on Improving Cognitive Function of the Elderly in Mongolato Village, Telaga District - Silvanda Lamaji; Rosmin Ilham; Nur Uyuun I. Biahimo (Universitas Muhammadiyah Palu, 2026)
One of the most significant declines in old age is the decline in cognitive abilities which include memory, attention, language and problem-solving. One of the non-pharmacological approaches used to improve the cognitive function of the elderly is puzzle therapy. This study aims to determine the effect of puzzle therapy on the improvement of cognitive function of the elderly. The research design used quantitative methods with the Quasi-Experimental method (Two-group Pretest-Posttest Control group design), the number of population, namely all elderly people who experienced dementia as many as 52 respondents while the number of samples was 34 elderly divided into 17 elderly people in the intervention group and 17 elderly in the control group, this study used the Wilcoxon test. The results of the study were the cognitive function of the elderly in the intervention group before being given the intervention, namely the weight category as many as 13 respondents, after the intervention was moderate, as many as 13 respondents while the cognitive function of the elderly in the control group before was the weight category as many as 14 respondents, after the weight category as many as 14 respondents, the results of the Wilcoxon test obtained a significant value of 0.000. In conclusion, there was an effect of puzzle therapy on improving the cognitive function of the elderly in Mongolato Village, Telaga District. Suggestions for officers in the village and their families to cooperate with the Puskesmas in providing therapy to the elderly to improve the cognitive function of the elderly.